2019
DOI: 10.1039/c9na00455f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and applications of electrochemical chemosensors based on carbon-nanomaterial-modified molecularly imprinted polymers

Abstract: The past few decades have witnessed a rapid development in electrochemical chemosensors (ECCSs). The integration of carbon nanomaterials (CNMs) and molecularly imprinted polymers (MIPs) has endowed ECCSs with high selectivity and sensitivity toward target detection. Due to the integrated merits of MIPs and CNMs, CNM-modified MIPs as ECCSs have been widely reported and have excellent detection applications. This review systematically summarized the general categories, preparation strategies, and applications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 215 publications
(182 reference statements)
0
29
0
2
Order By: Relevance
“…In this case, the resistance charge transfer (Rct) electrical element is usually affected by the events occurring at the electrode surface, such as the binding between a sensing receptor and its target [17].In order to obtain a sensor suitable for onsite testing, it is highly desirable to employ stable and robust sensing elements. Previous works have demonstrated that the use of molecularly imprinted polymers in electrochemical sensing can result in robust, sensitive and specific diagnostic systems [18][19][20]. Particularly, molecularly imprinted nanoparticles (nanoMIPs), prepared using a solid phase, have shown to be a powerful and robust mimic of antibodies in sensors and assays [21][22][23], while providing convenient and animal-free synthesis.…”
mentioning
confidence: 99%
“…In this case, the resistance charge transfer (Rct) electrical element is usually affected by the events occurring at the electrode surface, such as the binding between a sensing receptor and its target [17].In order to obtain a sensor suitable for onsite testing, it is highly desirable to employ stable and robust sensing elements. Previous works have demonstrated that the use of molecularly imprinted polymers in electrochemical sensing can result in robust, sensitive and specific diagnostic systems [18][19][20]. Particularly, molecularly imprinted nanoparticles (nanoMIPs), prepared using a solid phase, have shown to be a powerful and robust mimic of antibodies in sensors and assays [21][22][23], while providing convenient and animal-free synthesis.…”
mentioning
confidence: 99%
“…Thin MIP layers and nanomaterials improve mass transfer addressing challenges related to effective template removal and analyte binding (46). Conductive nanomaterials and MIPs synergistically improve biosensor efficacy by reducing the latter's insulating nature and mitigating the former's inherent dispersal and toxicity challenges (167). Another MIP biosensor challenge, limited selection of monomers and crosslinkers for custom analyte binding, is mitigated through intelligent application of computer modeling (103) and adoption of SNMs as nanocarrier (166).…”
Section: Discussionmentioning
confidence: 99%
“…Many MIP-based nanobiosensors adopt silica as the functional monomer matrix for containing selective binding sites for the target analyte (166,167). Silica readily adapts itself to this application as a result of its biocompatibility, facile functionalization through silanization, potential for periodic porosity, high surface area to volume ratio, tunable pore size, and chemical stability.…”
Section: Silica Nanomaterials (Snms)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past three years, a series of excellent reviews focused on the preparation [5][6][7] and application of MIPs [8][9][10][11][12][13][14][15][16][17][18] have been published. In those review articles, 2,6,7 the brief history of the molecular imprinting technique, the type of molecular imprinting (including noncovalent imprinting, covalent imprinting, semicovalent imprinting), and the essential elements of molecular imprinting like functional monomer, cross-linker, target template, initiators and porogens have been introduced in detail many times.…”
Section: Introductionmentioning
confidence: 99%